The right to forgetting as a fundamental guarantee to the resocialization of psychopathic criminals (Research, Society and Development, 2020)
The present study deals with the right to forgetfulness and its incidence in the resocialization of psychopaths. The studies followed over time with the need to characterize and know, first, psychopathy, and find solutions to problems, but all evolution on the subject served as a multidisciplinary mosaic and a more consistent study in our present day. The resocialization of psychopathic criminals is revealed as an apparent utopia, and the necessary psychological treatment of those affected by such disorders is far from being verified in praxis. In this perspective, this article, through exploratory research, of qualitative nature, deductive method, collection of bibliographic-documentary data, was carried out in order to perform an analysis about the alternatives of resocialization of psychopathic criminals as an individual and collective subjective right in favor of legal certainty, and the right to forget is a viable and necessary solution to effect this fundamental right. Finally, in view of the problem exposed, we sought, based on constitutional principles, to elucidate the need of the State, based on the defense of human dignity and respect for social well-being, seeking the application of the right to forgetfulness as a means of resocialization of psychopathic criminals in the current Brazilian prison system.